Wood use and forest management at the Late Bronze Age copper mining site of Prigglitz-Gasteil in the Eastern Alps – A combined anthracological, archaeological, and palynological approach. (December 2022) - Jakobitsch, Thorsten; Wiesinger, Silvia; Heiss, Andreas G.; Faltner, Felix; Oeggl, Klaus; Grabner, Michael; Trebsche, Peter
Highlights: The study combines archaeological, anthracological, and palynological data sources. Bronze Age mining impacted on the local forest, leading to secondary succession in small areas. Gathering of firewood followed the principle of least effort. We found evidence for a selective use of wood, but no hints of depletion of the forest. Conifer needles indicate additional (as yet unknown) usage patterns for fir and spruce. Abstract: The Late Bronze Age mining site of Prigglitz-Gasteil provides a wealth of sources of information for the reconstruction of wood use, past vegetation, and forest management at a copper production facility. In this paper we have combined charcoal analyses from domestic and workshop contexts and the investigation of mining timbers found in the backfill of the opencast copper ore mine with the first results from pollen analyses from the nearby Saubachgraben mire. The complementary information from these different contexts allowed a reconstruction of the impact of settlement and mining activities on the natural mixed forest around the site, chiefly composed of beech, spruce, and fir. Forest clearing affected mainly spruce. Despite the dominance of spruce among the conifers, however, fir wood was exclusively selected for the production of mining timbers, which were used to support the opencast mine walls or for water management constructions. The gathering of firewood for domestic hearths followed the principle of least effort, leading to a secondary succession with pioneering species in the immediate surroundings of the mining settlement. The investigated wood and charcoal finds indicated an intentional and selective use of the locally available wood species. At the current state of the investigations, there is no evidence of scarcity or shortage in the wood supply.